Diseño De Un Producto Agro-Ecoturístico En La Propiedad De La Empresa Agropecuaria Y Turística “A Y T” Parroquia San Isidro, Cantón Guano, Provincia De Chimborazo - Cutiupala, Guicela Margoth Ati; Baquero, Juan Carlos Carrasco; Arévalo, Paola Alexandra Velastegui; Vinueza, Sofía Andrea Basantes; Velásquez, Carlos Renato Chávez (European Scientific Journal, ESJ, 2016)
The development of an agro-ecotourism product in the A&T Agricola and touristic company was the objective of this research project. The first stage of this project consisted in the collection of primary and secondary information through field visits and literature review. It was identified that local and international tourist will be the target audience of this product (target demand). Furthermore, a complete inventory of touristic sites in the zone were created. This inventory identified five natural attractions and five cultural attractions, with five attractions reaching level II of hierarchy. To target tourist, four packages were designed using touristic and agro-ecological activities. In the second stage of this project, economic, legal, and environmental feasibility analyses will be performed. Finally, the agro-ecotourism product proposed in this project is an alternative for the development of the local population as it takes into account the local agriculture in conjunction with ecological activities targeted to the improvement of the society economically and culturally.